Induction and persistence of abnormal testicular germ cells following gestational exposure to di-(n-butyl) phthalate in p53-null mice - Saffarini, Camelia M. (2011)
Phthalate esters are commonly used plasticizers found in many household items, personal care products, and medical devices. Animal studies have shown that in utero exposure to di-(n-butyl) phthalate (DBP) within a critical window during gestation causes male reproductive tract abnormalities resembling testicular dysgenesis syndrome (TDS). Our studies utilized p53-deficient mice for their ability to display greater resistance to apoptosis during development. This model was chosen to determine whether multi-nucleated germ cells (MNGs) induced by gestational DBP exposure could survive postnatally and evolve into testicular germ cell cancer. Pregnant dams were exposed to DBP (500 mg/kg/day) by oral gavage from gestational day (GD) 12 until birth. Perinatal effects were assessed on GD 19 and postnatal days 1, 4, 7, and 10 for the number of MNGs present in control and DBP-treated p53-heterozygote and null animals. As expected, DBP exposure induced MNGs, with greater numbers found in p53 null mice. Additionally, there was a time-dependent decrease in the incidence of MNGs during the early postnatal period. Histological examination of adult mice exposed in utero to DBP revealed persistence of abnormal germ cells only in DBP-treated p53-null mice, not in p53-heterozygote or wild-type mice. Immunohistochemical staining of perinatal MNGs and adult abnormal germ cells was negative for both octamer binding protein-3/4 and placental alkaline phosphatase. This unique model identifies a role for p53 in the perinatal apoptosis of DBP-induced MNGs, and provides insight into the long-term effects of gestational DBP exposure within a p53-null environment.